A NEW SPECIES OF TELMATOBIUS WIEGMANN, 1834, FROM THE EASTERN CORDILLERA CENTRAL OF THE ANDES, PERU. (ANURA: TELMATOBIIDAE), WITH DESCRIPTION OF ITS TADPOLE, AND RANGE EXTENSION OF T. MENDELSONI DE LA RIVA ET AL., 2012 - Ttito, A (2016)
This study was partially funded by projects CLG2008-04164 and CLG2011-30393 of the Spanish government (PI: I. De la Riva), and the International Cooperation Project funded by the Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica (CONCYTEC, Peru) throught Fondo Nacional de Desarrollo Cientifico, Tecnologico y de Innovacion Tecnologica (FONDECYT, Peru) and the Ministerio de Ciencia, Tecnologia e Innovacion Productiva (MINCyT, Argentina) (PI. Juan C. Chaparro).